URGENSI PENGGUNAAN MEDIA PEMBELAJARAN DALAM MEMPELAJARI MATERI BIOLOGI - Nur Lina Safitri; Nuril Hidayati (Universitas Nahdlatul Ulama Pasuruan, 2023)
Learning requires an intermediary to help students understand the material being studied. This study aims to determine student perceptions related to the urgency of using learning media in learning biology material. This research uses a survey method. The survey was conducted to undergraduate Biology Education Study Program students in semesters 2, 4, 6, and 8. The subjects of this study were taken from students who had not, were and had received learning media development courses. Students were given questionnaires online. Based on the research conducted, the results show that 61.5% of students strongly agree that biology learning uses learning media. In addition, 59% of students think that by using learning media students have more learning experiences. These results show that undergraduate students of Biology Education ITSNU Pasuruan already have an awareness that the use of learning media in learning biology material is very important.